PENGARUH PEMBELAJARAN BERBASIS BUDAYA LOKAL TERHADAP ETIKA DAN KEDISIPLINAN PESERTA DIDIK DI SD NEGERI CINANGGUNG KOTA SERANG - Umdawiyah Umdawiyah; Asep Muhyidin; Aan Asphianto; Ujang Jamaludin (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of local culture-based learning on students’ ethics and discipline at SD Negeri Cinanggung, Serang City. This study employed a quantitative approach with an explanatory research design. The sample consisted of 200 students from grades IV, V, and VI. Data were collected using a closed-ended questionnaire with a Likert scale and analyzed through descriptive analysis and linear regression using the SPSS program. The descriptive analysis results showed that local culture-based learning was in the high category, with a mean score of 4.16, while students’ ethics had a mean score of 4.12 and students’ discipline had a mean score of 4.14. The regression analysis results showed that local culture-based learning had a positive and significant effect on students’ ethics, with a regression coefficient of 0.696 and a significance value of 0.000 < 0.05. Local culture-based learning also had a positive and significant effect on students’ discipline, with a regression coefficient of 0.729 and a significance value of 0.000 < 0.05. The coefficient of determination indicated that local culture-based learning explained 42.6% of the variance in students’ ethics and 45.0% of the variance in students’ discipline. These findings indicate that integrating local cultural values into learning can serve as a relevant strategy for shaping students’ polite, honest, responsible, orderly, and rule-abiding behavior.